The Influence of Artificial Intelligence and Teacher Leadership on Science Major Students - Kusman Sudibyo (Jurnal Penelitian Pendidikan IPA, 2024)
This research will analyze the use of Artificial Intelligence (AI) and teacher leadership on student performance. Another variable analyzed was the use of books and demonstrations in the form of PowerPoint presentations. Apart from that, in this research two moderator variables will also be used, namely devices and illustrations in PowerPoint. The tools used by teachers are expected to be able to increase the influence of book use on student performance and also improve relationships between leadership. The illustrative moderator variable turned out to increase the effect of using PowerPoint on student performance. In this research it is proven that AI can improve the leadership of teachers, and teacher leadership will improve student performance. Leadership will also have a stronger influence on performance if teachers use the right devices, whether notebooks, tablets or cellphones. Apart from that, the use of presentations created with PowerPoint will also improve student performance. When accompanied by illustrations (especially transitions and animations). Therefore, teachers must be able to utilize AI and its supporting applications